Mechanisms of Charge Storage in Nanoparticulate TiO2 and Li4Ti5O12 Anodes: New Insights from Scan rate-dependent Cyclic Voltammetry. (20th June 2015) - Opitz, Martin; Yue, Junpei; Wallauer, Jens; Smarsly, Bernd; Roling, Bernhard
Abstract: We have studied Li intercalation into two nanoparticulate anode materials for lithium ion batteries, namely Nb-doped TiO2 (Nb-TiO2 ) and Li4 Ti5 O12 (LTO), by means of scan rate-dependent cyclic voltammetry. The average particle size is 7 nm for Nb-TiO2 and 6 nm for LTO, respectively. For both materials, we observe a transition in the scan rate dependence of the charge flow, namely from Li intercalation capacity control at low scan rates to diffusion/phase transformation control at higher scan rates. The peak current densities exhibit an approximate power law dependence on the scan rate with exponents between 0.54 and 0.64, even for low scan rates at which the charge flow is close to the Li intercalation capacity. Furthermore, we have tested a method proposed in the literature for differentiating between Faradaic and pseudocapacitive charge storage from scan rate-dependent cyclic voltammograms. The obtained results are not physically meaningful, in particular the obtained negative pseudocapacitive and Faradaic currents. We have analysed the origin of these results, and we show that iso-potential plots of the scan rate-dependent current are not suitable for differentiating between Faradaic and pseudocapacitive processes.